Gambaran Self Regulated Learning Pada Mahasiswa yang Telah Menyelesaikan Skripsi - Diana Anindita; Afifah Rahmania; Dewi Khurun Aini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research aims to determine the description of self-regulated learning that has completed its thesis. The approach used is a qualitative approach with a narrative biography research type. The subjects in this research are the subjects in this research who are participants based on predetermined criteria. The data collection technique used in this research was a semi-structured interview technique. Based on the research results, the picture of self-regulated learning for those who have completed their thesis is reflected in several factors (1) the ability to manage time (2) managing stress and maintaining motivation are important factors in completing the thesis. (3) social support from parents, supervisors and the surrounding environment also plays an important role in motivating students to complete their thesis.